Model reduction design for continuous systems with finite frequency specifications - Miloud Koumir; Abderrahim El-Amrani; Ismail Boumhidi (International Journal of Electrical and Computer Engineering (IJECE), 2021)
This paper is concerned with the problem of model reduction design for continuous systems in Takagi-Sugeno fuzzy model. Through the defined FF H∞ gain performance, sufficient conditions are derived to design model reduction and to assure the fuzzy error system to be asymptotically stable with a FF H∞ gain performance index. The explicit conditions of fuzzy model reduction are developed by solving linear matrix inequalities. Finally, a numerical example is given to illustrate the effectiveness of the proposed method.